PreStatistics - Donald Davis (Cengage Learning, 2018)
PRESTATISTICS prepares students for statistics with a three-step problem-solving process that shows them how to identify the method needed to solve a given problem, use mathematics to find a numerical result and interpret that result. Authors Davis, Armstrong and McCraith highlight why each section's concepts are useful to learn and engage students with many real-data applications.